Talon cusp in a primary lateral incisor from a medieval child - S. MAYS (Paediatric Dentistry, 2005)
This paper describes talon cusp in an ancient skeleton and is a rare report of its occurrence in a primary lateral incisor. As well as talon cusp, the affected incisor also shows abnormal widening, probably representing a double tooth. There is also a supernumerary permanent incisor.